Understanding Methods for Estimating HIV-Associated Maternal Mortality - James E. Rosen; Isabelle de Zoysa; Karl Dehne; Viviana Mangiaterra; Quarraisha Abdool-Karim (Journal of Pregnancy)
The impact of HIV on maternal mortality and more broadly on the health of women, remains poorly documented and understood. Two recent reports attempt to address the conceptual and methodological challenges that arise in estimating HIV-related maternal mortality and trends. This paper presents and compares the methods and discusses how they affect estimates at global and regional levels. Country examples of likely patterns of mortality among women of reproductive age are provided to illustrate the critical interactions between HIV and complications of pregnancy in high-HIV-burden countries. The implications for collaboration between HIV and reproductive health programmes are discussed, in support of accelerated action to reach the Millennium Development Goals and improve the health of women.